HSP27 Inhibits Homocysteine-Induced Endothelial Apoptosis by Modulation of ROS Production and Mitochondrial Caspase-Dependent Apoptotic Pathway. (17th April 2016) - Tian, Xin; Zhao, Lei; Song, Xianjing; Yan, Youyou; Liu, Ning; Li, Tianyi; Yan, Bingdi; Liu, Bin
Abstract : Objectives . Elevated plasma homocysteine (Hcy) could lead to endothelial dysfunction and is viewed as an independent risk factor for atherosclerosis. Heat shock protein 27 (HSP27), a small heat shock protein, is reported to exert protective effect against atherosclerosis. This study aims to investigate the protective effect of HSP27 against Hcy-induced endothelial cell apoptosis in human umbilical vein endothelial cells (HUVECs) and to determine the underlying mechanisms. Methods . Apoptosis, reactive oxygen species (ROS), and mitochondrial membrane potential (MMP) of normal or HSP27-overexpressing HUVECs in the presence of Hcy were analyzed by flow cytometry. The mRNA and protein expression levels were measured by quantitative real-time polymerase chain reaction (qRT-PCR) and western blot. Results . We found that Hcy could induce cell apoptosis with corresponding decrease of nitric oxide (NO) level, increase of endothelin-1 (ET-1), intracellular adhesion molecule-1 (ICAM-1), vascular cellular adhesion molecule-1 (VCAM-1), and monocyte chemoattractant protein-1 (MCP-1) levels, elevation of ROS, and dissipation of MMP. In addition, HSP27 could protect the cell against Hcy-induced apoptosis and inhibit the effect of Hcy on HUVECs. Furthermore, HSP27 could increase the ratio of Bcl-2/Bax and inhibit caspase-3 activity. Conclusions . Therefore, we concluded that HSP27 played a protective role against Hcy-induced endothelial apoptosis through modulation of ROS production and the mitochondrial caspase-dependent apoptotic pathway.